Pembangunan Kerohanian Usahawan Melayu di Malaysia : Tinjauan dari Perspektif Guru-Guru Murshid: Spiritual Development of Malay Entrepreneurs in Malaysia: A Perspective From Murshid Teachers - Abdul Kadir, Abu Yazid; Mohammed Zabidi , Ahmad Fakhrurrazi; Yaacob , Salmy Edawati (‘Abqari Journal, 2022)
Spirituality is the most important aspect in a person of Malay entrepreneurs. The spiritual system of an entrepreneur which consists of heart, passion, intellect and spirit needs to be developed through the method of guidance of a murshid teacher. Failure Malay entrepreneurs to develop a system of spirituality is caused by a lack of spiritual practices such as mysticism, suhbah, manners, remembrance, fasting, prayer, charity and muraqabah. This study will examine these factors in depth, especially for entrepreneurs with secular and non -secular entrepreneurs. Thus, this study aims to explore the spiritual practices from the point of view of murshid teachers who bring success in the field of entrepreneurship in Malaysia. This study is qualitative in nature by taking a content analysis approach and in -depth interview method. The results of the study found that spiritual practices influence the personal nature of entrepreneurs, build self -confidence, build self -defense systems, and form noble morals. In addition, spiritual practice also helps to aspects of self -management and business that are more beneficial to lead to success in this world and in the hereafter. ABSTRAK Kerohanian merupakan aspek paling penting dalam diri seseorang usahawan Melayu. Sistem kerohanian seorang usahawan yang terdiri daripada hati, nafsu, akal dan roh perlu di bangunkan melalui kaedah bimbingan seorang guru murshid. Kegagalan usahawan Melayu untuk membangunkan sistem kerohanian adalah disebabkan oleh faktor kekurangan amalan kerohanian seperti suluk, suhbah, adab, zikir, puasa, solat, zakat dan muraqabah. Kajian ini akan meneliti faktor tersebut secara mendalam khususnya terhadap usahawan bertarekat dengan usahawan tidak bertarekat. Justeru, kajian ini bertujuan untuk meneroka amalan-amalan kerohanian dari sudut pandang guru-guru murshid yang membawa kejayaan dalam bidang keusahawanan di Malaysia. Kajian ini berbentuk kualitatif dengan mengambil pendekatan analisis kandungan dan kaedah temubual mendalam. Hasil kajian mendapati amalan kerohanian mempengaruhi sifat peribadi usahawan, membina keyakinan diri, membina sistem pertahanan diri, dan membentuk akhlak mulia. Di samping itu, amalan kerohanian turut membantu kepada aspek pengurusan diri dan perniagaan yang lebih bermanfaat sehingga membawa kepada kejayaan di dunia dan di akhirat kelak.